The Forgotten Subject Subject Constitutions in Mediatized Everyday Worlds - Gentzel, Peter; Krotz, Friedrich; Wimmer, Jeffrey; Winter, Rainer (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Palgrave Macmillan, 2023)
The volume provides a critical inventory of existing concepts of the subject in communication studies research. In addition, concepts are developed in order to be able to analyze subjectivity in the context of current theoretical debates (including media sociology, cultural studies, psychoanalysis, practice theory, science and technology studies) as well as social, cultural and technical developments (including digitalization, mediatization, mobility and networking). Since subject conceptions are of central importance for any communication and media analyses, the volume fills a central gap in communication and media studies. The Content Subject conceptions in communication studies research and in the light of current developments in social and cultural studies.- Empirical analyses of the meaning of subjectivity and identity in and for digital(r) communication in mediatized worlds. The target groups - Communication and media scientists, sociologists, cultural scientists, pedagogues, technology scientists - Specialists and executives in associations, politics and business The editors Dr. Peter Gentzel is juniorprofessor at the University of Erlangen-Nuremberg Dr. Friedrich Krotz is professor (emer.) at the Center for Media, Communication and Information Research (ZeMKI) at the University of Bremen. Dr. Jeffrey Wimmer is a professor at the Institute for Media, Knowledge and Communication at the University of Augsburg. Dr. Rainer Winter is a professor at the Institute for Communication Studies at the University of Klagenfurt. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Introduction -- How does communicating constitute the human being? -- The subject of communicative action, subjectivity and subjectification -- From social interaction to digital networking -- Materiality, technology and the subject: elements of critical communication and media analysis -- Media use and psychoanalysis: theoretical and empirical perspectives -- Subjectification in datafied societies -- Narrative subject constructions in the sign of media and socio-cultural change. Narrative subject constructions in the sign of medial and socio-cultural change -- From subject to user, - and back? -- The history of media-based technologies of the self from Rousseau to Runtastic -- Subject enactment and communication power digital -- On the mediality of pedagogical relations and the medial side of education -- Memes as image-mediated subjectification practices.
Keywords: Communication; Mass media; Culture -- Study and teaching; Media and Communication; Media Sociology; Cultural Studies